Evaluation of glycemic index determination method - Ratna Sari Listyaningrum; Didah Nur Faridah; Puspo Edi Giriwono; Masayu Nur Ulfa (Universitas Ahmad Dahlan, 2021)
In Indonesia, determination of glycemic index (GI) was performed according to approved protocols prescribed by FAO (1998) and BPOM (2011); but, remarkable differences among these methods exist, primarily regarding the points of recommendation. This present work aimed to evaluate the technical steps of the protocol for determining GI between two protocols recommended by BPOM (2011) and FAO (1998). Ten healthy subjects (age 21-36 years old and body mass index (BMI) 18.5-24.9 kg/m2) were recruited for the study. The blood glucose was measured with repeated glucose trials, while the number of sampling points for the blood glucose test was also investigated. The range of GI for rice, wheat cookies, NS-cookies, HMT-cookies were 68 – 77; 55 – 60; 35 – 43; 35 – 41, respectively, using the combination of three different aspects between FAO and BPOM protocol. Noticeably, the difference in glucose trials did not cause significant variations to GI (n=10, p>0.05). Regarding statistical performance between methods, the Coefficient of Variance (CV) resulted from BPOM protocol (10 subjects, 5 sampling points) ranged 37 to 49%, being slightly higher compared to CV obtained from FAO protocol (7 subjects with triplicate glucose trials, 7 sampling points), i.e., 33% and 35%. The conclusive remark was noticed, that the most satisfying protocol for determination of GI was achieved using no less than two reference food trials, seven subjects, and seven blood sampling points.